33.5k views
5 votes
2 (k - 5) + 3k = k + 6

User Boxxar
by
5.1k points

2 Answers

1 vote

Answer:

4

Explanation:

2(k-5)+3k = k+6

using BODMAS we remove the bracket first

(2*k)-(2*5)+3k = k+6

2k-10+3k = k+6

collecting like terms we have

2k+3k-k = 10+6

5k-k = 10+6

4k =16

divide both sides by the coefficient of k I.e 4

therefore ,k =4

User Yoavmatchulsky
by
4.5k points
3 votes

Answer:

k=4

Explanation:

First, distribute the 2 on the left side

2 (k - 5) + 3k = k + 6

2*k +2*-5 +3k=k+6

2k-10+3k=k+6

Combine like terms on the left side

5k-10=k+6

Add 10 on both sides

5k=k+16

Subtract k on both sides

4k=16

Divide by 4 on both sides

k=4

Hope this helps! :)

User Hadronzoo
by
5.1k points